Role of The DPR RI in Its Function Budgeting in State Financial Management - Querida Paraninda Pandan Arum; Nuria Siswi Enggarani (Universitas Muhammadiyah Surakarta, 2026)
The House of Representatives of the Republic of Indonesia (DPR RI) holds a strategic position in state financial management, particularly through the implementation of its budgetary function, which includes budgetary rights. This study focuses on analyzing the DPR RI's role in carrying out this budgetary function, both based on statutory provisions and in practice. The approach used in this research is normative juridical, emphasizing the study of applicable legal norms.Research findings indicate that in the budgeting process, the Indonesian House of Representatives (DPR RI) has the authority to discuss and approve the Draft State Budget Law (RUU APBN) with the President. This authority is exercised through the DPR's internal apparatus, specifically the Budget Agency (Banggar) and relevant commissions. The legal basis for this mechanism is stated in Article 110 paragraphs (1) and (2) of the MD3 Law. On the other hand, the DPR Ethics Council (MKD) acts as a complementary body responsible for maintaining the integrity, ethics, and honor of DPR members. In the context of the budgeting function, the existence of the MKD has its own significance because every decision related to the budget has a direct impact on state financial governance and the interests of the wider community.